Molecular dynamics study of grain boundaries as defect sinks under irradiation in LiAlO2 and LiAl5O8 - Ankit Roy; Weilin Jiang; Giridhar Nandipati; Andrew M. Casella; David J. Senor; Ayoub Soulami; Ram Devanathan (npj Materials Degradation)
Abstract Lithium aluminate ceramics, LiAlO2 and LiAl5O8, show promise in nuclear environments due to their excellent radiation tolerance. Molecular dynamics simulations investigate grain boundaries (GB) and their role in defect evolution. Results reveal that GBs act as efficient defect sinks, with Li and Al atoms exhibiting distinct behaviors during displacement cascades. Tritium migration in LiAlO2 is also studied, showing rapid diffusion and stable configurations with oxygen, corroborated by ab initio simulations from the literature. The calculated tritium diffusion coefficient of 1.33 × 10−¹⁴ m²/s aligns with the literature, validating the model. LiAl5O8 demonstrates superior defect healing compared to LiAlO2, attributed to enhanced atomic transfer between grains and GBs. These findings reveal key insights into defect dynamics, providing essential insights for their application in tritium-producing burnable absorber rods (TPBARs).